1992
DOI: 10.1161/01.res.71.6.1294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of serotonin on intracellular pH and contraction in vascular smooth muscle.

Abstract: Serotonin (5-HT) and other contractile agonists stimulate Na(+)-H+ exchange in vascular smooth muscle. Since intracellular alkalinization, per se, stimulates contraction, we tested whether 5-HT-induced contraction was associated with an increased pHi. In HCO3(-)-free buffer (pHo 7.4), 5-HT (10(-5) M) increased pHi, as measured by 2',7'-bis(2-carboxyethyl)-5(6)-carboxyfluorescein fluorescence, from 7.10 +/- 0.03 to 7.34 +/- 0.03 (p < 0.01) in primary cultures of canine femoral artery vascular smooth muscle cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
4
15
0
Order By: Relevance
“…We predicted that we would see an increase in MAP upon injection of 5-HT and norepinephrine because both of these neurotransmitters are known to cause vasoconstriction (Vanhoutte, 1974;Kahn et al, 1992) whereas ACh does not (Kirby and Burnstock, 1969;Vanhoutte, 1974). Our data match these predictions.…”
Section: Cardiovascular Variablessupporting
confidence: 77%
“…We predicted that we would see an increase in MAP upon injection of 5-HT and norepinephrine because both of these neurotransmitters are known to cause vasoconstriction (Vanhoutte, 1974;Kahn et al, 1992) whereas ACh does not (Kirby and Burnstock, 1969;Vanhoutte, 1974). Our data match these predictions.…”
Section: Cardiovascular Variablessupporting
confidence: 77%
“…8 We have previously shown that the cells in this preparation are contracted by serotonin in a dose-dependent, inhibitable, and reversible manner. 8 The dishes were placed on the heated (37°C) stage of a Nikon Diaphot inverted phase-contrast microscope, and the culture medium was replaced with a physiological salt solution that contained (mmol/L) NaCl, 140; KC1, 4; CaCl 2 , 2; MgCl 2 , 1; glucose, 5; and HEPES-Tris, 10, pH 7.4 (HEPES PSS) plus 4% bovine serum albumen (BSA), with or without bovine insulin (40 juU/mL) (Sigma) (Figs 2 through 4 and 6 through 8). After 20 minutes, a field of at least 6 to 10 cells was photographed at x200 to obtain baseline images.…”
Section: Cell Contractionmentioning
confidence: 74%
“…The dispersed cells were pelleted and washed three times in Hanks' balanced salt solution (GIBCO, Grand Island, NY) and suspended to a density of 2X10 3 cells per milliliter in Dulbecco's modified Eagle's medium (DMEM) that contained 0.5% fetal calf serum, 1% glutamine, and 1% penicillin-streptomycin solution (10 000 U/mL penicillin, 10 mg/mL streptomycin, Sigma). One milliliter of this suspension was placed in 35-mm culture dishes on top of rat tail tendon collagen gels, which were prepared as follows 8 : Sprague-Dawley rat tail tendons were sterilized in 70% ethanol for 4 hours, minced, and extracted with 0.1% acetic acid for 48 hours at 4°C. The protein concentration of the supernatant was adjusted to 0.15 mg/mL and titrated to pH 8.0 with NaOH at 4°C.…”
mentioning
confidence: 99%
“…Contraction was measured on the basis of the methods described by Kahn et al 27 and Bodin et al 28 Cells were loaded with fura-2-acetoxymethyl ester (4 mol/L) for [Ca 2ϩ ] i or BCECF (0.2 mol/L) for pH i , as described in detail previously. 16,29 Single cells in cell clusters were investigated using an Axiovert 135 inverted microscope (ϫ40 oil-immersion objective) and an Attofluor digital fluorescence system (Zeiss) using alternating excitatory wavelengths of 343 and 380 nm for [Ca 2ϩ ] i measurements and 440 and 495 nm for pH i measurements.…”
Section: Simultaneous Measurement Of Vascular Smooth Muscle Cell [Ca mentioning
confidence: 99%
“…The magnitude of cell contraction was expressed as the percentage reduction in cell length relative to initial baseline measurements. 16,27,28 For each cell, the percentage contraction from the baseline was calculated, and these values were averaged for all cells. The average basal cell measurements were consistent between preparations.…”
Section: Simultaneous Measurement Of Vascular Smooth Muscle Cell [Ca mentioning
confidence: 99%